Efektivitas Pelaksanaan Peraturan Bupati Karangasem Nomor 42 Tahun 2020 dalam Upaya Pencegahan dan Pengendalian Covid-19 di Kabupaten Karangasem - Ni Made Sasmita Ayuningrum; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Currently the Karangasem Regency government is trying to reduce the positive number of Covid-19 in Karangasem Regency which has increased quite drastically, so the Karangasem Regent issued Regent Regulation Number 42 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort for Prevention and Control of Coronavirus Disease 2019 in New Era Life Order. This research was conducted to examine the effectiveness of the implementation of the Karangasem Regent's Regulation Number 42 of 2020 in an effort to prevent and control Covid-19 in Karangasem Regency. The research method used is empirical legal research. This research applies a field approach, a Legislative approach, and a case approach. Sources of data used in the form of primary legal data and secondary legal data. The data analysis method used is a qualitative method. The results of this study indicate that the implementation of the Karangasem Regent's Regulation Number 42 of 2020 in controlling Covid-19 in Karangasem Regency has gone well according to the applicable laws and regulations. Factors inhibiting the implementation of the Karangasem Regent's Regulation Number 42 of 2020 in an effort to prevent Covid-19 in Karangasem Regency There are internal factors and external factors, so that in terms of community compliance in obeying the rules, it is very important.